21st century Latin American synthetic peptides for their application in antivenom production - Jésica A. Rodríguez; Gabriela R. Barredo-Vacchelli; Joaquin A. Eloy; Silvia A. Camperi (Exploration of Drug Science)
Envenomation caused by snakes, scorpions, and spiders represents a serious public health problem in Latin America. The antivenoms used for its treatment are produced by immunizing horses repeatedly with sublethal doses of animal venoms along with the adjuvant. However, venom availability is a bottleneck. Furthermore, toxin-neutralizing antibodies are only a few of the total produced with this classical method. Therefore, high doses of antivenom are required to achieve the neutralization power, which usually causes adverse reactions in the patient. With the aim of obtaining a higher proportion of toxin-neutralizing antibodies while reducing the dependency on venom availability, alternative immunization protocols have been explored using synthetic peptides with epitopes from clinically relevant toxins. The process to design an immunogenic peptide entitles: (a) choice of the medical relevant toxins in the venom; (b) identification of the epitopes in the selected toxins; (c) improvement of peptide immunogenicity; (d) immunogen synthesis; and e) in vitro and in vivo evaluation. The present article aims to review the advances in the design of immunogenic synthetic peptides for their application in antivenom production in Latin America during the 21st century. Epitopes have been identified from many clinically important toxins in Latin American snakes (snake venom metalloproteinases, snake venom serine proteases, crotamine, phospholipases A2, and three-finger toxins), scorpions (beta-mammal/insect toxin Ts1, alpha-mammal toxin Ts2, alpha-mammal toxin Ts3, toxin Ts4, and beta-mammal Tt1g neurotoxin), and spiders (dermonecrotic toxin and delta-ctenitoxin-Pn2a). Nevertheless, their application is still experimental, even though they are ideal for large-scale and low-cost antivenom production, factors that are necessary to meet national and regional demands.